SUBCUTANEOUS ONLAY LAPAROSCOPIC APPROACH (SCOLA) FOR VENTRAL HERNIA AND RECTUS ABDOMINIS DIASTASIS REPAIR: TECHNICAL DESCRIPTION AND INITIAL RESULTS - CLAUS, Christiano Marlo Paggi (Arq Bras Cir Dig, 2018)
BACKGROUND: Diastasis of the rectus abdominis muscles (DMRA) is frequent and may be associated with abdominal wall hernias. For patients with redudant skin, dermolipectomy and plication of the diastasis is the most commonly used procedure. However, there is a significant group of patients who do not require skin resection or do not want large incisions. AIM: To describe a “new” technique (subcutaneous onlay laparoscopic approach - SCOLA) for the correction of ventral hernias combined with the DMRA plication and to report the initial results of a case series. METHOD: SCOLA was applied in 48 patients to correct ventral hernia concomitant to plication of DMRA by pre-aponeurotic endoscopic technique. RESULTS: The mean operative time was 93.5 min. There were no intra-operative complications and no conversion. Seroma was the most frequent complication (n=13, 27%). Only one (2%) had surgical wound infection. After a median follow-up of eight months (2-19), only one (2%) patient presented recurrence of DMRA and one (2%) subcutaneous tissue retraction/fibrosis. Forty-five (93.7%) patients reported being satisfied with outcome. CONCLUSION: The SCOLA technique is a safe, reproducible and effective alternative for patients with abdominal wall hernia associated with DMRA.